Qualitative Identification of Intervening Factors Affecting Digital Marketing Strategies in Successful Iranian Startups - Moradi, Sepideh; Abbasi, Javad; Radfar, Reza; Abdolvand , Mohamad Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The study aims to identify and analyze the key intervening factors that influence the digital marketing strategies of successful Iranian startups. It seeks to understand how these factors contribute to the effectiveness and efficiency of digital marketing efforts in the startup ecosystem of Iran.Methods and Materials: Employing a qualitative research design, the study conducted in-depth interviews with 12 digital marketing experts from various successful Iranian startups. Grounded theory methodology was used to analyze the interview data, facilitating the identification of core themes and factors affecting digital marketing strategies.Findings: The research identified several critical factors impacting digital marketing strategies, including organizational culture, technological adoption, market dynamics, and regulatory environment. It highlights the importance of adaptability, strategic alignment, and continuous learning within startups to navigate the challenges and opportunities of digital marketing.Conclusion: The study concludes that for Iranian startups, a nuanced understanding of both internal and external factors is crucial for developing and implementing effective digital marketing strategies. It underscores the need for a strategic approach that incorporates flexibility, innovation, and customer engagement to achieve sustained growth and competitive advantage in the digital marketplace.